OPTIMISING THE SELECTIVE TOOTH GRINDING PROTOCOL FOR PATIENTS WITH GENERALISED PERIODONTITIS (Ustozlar uchun, 2026)
Twenty individuals with Stage I–II generalised periodontitis in the remission phase, ages 35–55, participated in the research. During the supportive treatment phase, all patients had their teeth selectively ground. The procedure for the examination comprised:Clinical assessment of the state of periodontal tissue (PMA index, PI index, periodontal pocket depth).Using the conventional approach (articulating paper, 40–100 μm), premature contacts and occlusal interferences are identified.